Analisa Rasio Keuangan Likuiditas, Profitabilitas dan Solvabilitas Terhadap Kebijakan Pembayaran Dividen Penyertaan - Setiana, Anna; Melania, Indah (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
The purpose of this study is to find out the effect of the company’s performance to the welfare of shareholders by way of measuring the level of the company’s financial ratio expected having influence toward the dividend level yielded. Based on the result of the study, the liquidity of PT Estika Yasakelola can be said has not satisfied yet because, observed from current ratio and quick ratio, PT Estika Yasakelola has found it difficult to pay short term debt that has been due date. Viewed in general, the profitability percentage has not been satisfactory as well. It’s due to the percentage of net profit margin is too low, with the result that income left to cover the operational cost is too small. To improve the performance of of the company, PT Estika Yasakelola has to work more efficiently. The company must seek to improve cost efficiency by lowering cost items or increasing product selling price without reducing the competitiveness of the company. The description of solvency ratio fluctuation above reflects that the stability increase of the company in managing its dect is due to outstanding credit decrease caused by on time credit payment and because of the company keep continue to expand with its own fund. The result of this research shows that the company should improve its performance more, work more efficiently, reduce cost items or increase product selling price so that the company will be able to reduce operational costs. PT Estika yasakelola must be able to manage the fund, so that the company’s profit increases more and more and the company will be able to survive unwaveringly. The management must be able to maintain the sharekolders’ trust. Therefore, the level of shareholders’ welfare can be guaranteed. Keywords: analysis of financial liquidity ratio; profitability, and solvency